2018
DOI: 10.1080/01488376.2018.1477697
|View full text |Cite
|
Sign up to set email alerts
|

Defining Success: The Perspective of Emerging Adults with Foster Care Experience

Abstract: Youth with experience in the foster system are often more susceptible to negative outcomes in adulthood due to their high levels of cumulative risk. The present study sought out to redefine the concept of "success" from the perspective of emerging adults with experience in the foster care system and to identify patterns among the characteristics and behaviors of foster families that promote success as these young adults transition out of the foster care system and into adulthood. Participants most frequently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In support of this shift, recent research has found that youth in foster care reported high scores on developmental assets such as positive identities, healthy boundaries, and support from outside caregivers (e.g. Anderson & Williams, 2018;Diehl et al, 2011).…”
Section: Positive Youth Developmentmentioning
confidence: 99%
“…In support of this shift, recent research has found that youth in foster care reported high scores on developmental assets such as positive identities, healthy boundaries, and support from outside caregivers (e.g. Anderson & Williams, 2018;Diehl et al, 2011).…”
Section: Positive Youth Developmentmentioning
confidence: 99%
“…Williams [40] 2) USA Results indicate that the definition of "success" is complex and subjectively defined based on personal goals and that specific Developmental Assets are important for foster families to promote youth resilience.…”
Section: ) Anderson Andmentioning
confidence: 99%
“…Research that explores the concept of Developmental Assets in emerging adults is analyzed through this review, which indicates the predominance of the adoption of the Developmental Assets model developed by the Search Institute, with the operationalization of the concept that adopts assessment instruments developed based on the same model [24][25][26][27][28][39][40][41][42] . Thus, the Development Assets model that emerged by the Search Institute, initially applied to the adolescent population [43,44] , has gained increasing relevance in the emerging adult population.…”
Section: Conceptualization and Operationalization Of The Concept Of D...mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies focused on negative and positive outcomes in a foster care context mainly used a qualitative approach investigating the resilience process ( Parry and Weatherhead, 2014 ; Anderson and Williams, 2018 ), academic outcomes ( Rios and Rocco, 2014 ), subjective experiences of “aging out” of emancipated foster youth (e.g., economic challenges and housing instability, loss of social support, and pressure to be self-reliant; Cunningham and Diversi, 2013 ) and relational outcomes ( Berzin et al, 2014 ; Tyrell and Yates, 2018 ). Little is known about Italian youth with an out-of-home care background context ( Corradini, 2018 ).…”
Section: Introductionmentioning
confidence: 99%